Here, there and everywhere: my life recording the music of the Beatles - Emerick, Geoff 1945-2018 (Avery, 2007)
An engineer who worked with the Beatles during the productions of "Revolver," "Sgt. Pepper's Lonely Hearts Club Band," and other albums describes his innovative recording techniques, and shares his insights into the band's creative processes.